The Influence of Word of Mouth, Product Quality, and Perception of Benefits on the Decision to Purchase, with Consumer Trust as a Mediator (Jurnal Manajemen Bisnis, 2024)
Consuming milk is part of a healthy lifestyle for people worldwide, including in Indonesia. Among mammal milk types, goat's milk offers greater benefits. In Indonesia, the milk market, particularly for maintaining bone strength with high calcium content, is quite popular. The variety of goat milk products encourages consumers to assess them, influencing purchase interest and decisions. This research aims to determine the impact of word of mouth, product quality, and perceived benefits on Etawa Goat Milk purchasing decisions, with consumer trust as a mediator. The sample consisted of 150 active Etawa milk (Provit) consumers. Data was collected via questionnaires distributed through Google Forms using a 1-10 interval scale. Data analysis employed the Partial Least Squares approach using structural equation modeling. The findings reveal that word of mouth, product quality, and perceived benefits positively influence purchasing decisions, mediated by consumer trust. This research provides insights into improving Etawa milk (Provit) product quality to enhance consumer purchasing decisions.